â€œSUBSTITUSI MUNG BEAN MILK TERHADAP FULL CREAM MILK DALAM PEMBUATAN PANNA COTTAâ€: - - Ita Karnita; ghini kunthala devi; Muhamad Farhan (JURNAL PARIWISATA VOKASI, 2022)
The purpose of this research is to make pannacotta. This research is aimed at making a pannacotta product that has the same taste,aroma,texture and color as the comparative pannacotta but has a low fat content and is suitable for consumption by flextrians. Dessert is a dish that is served as a dessert or at the end of a buffet or a'la carte meal which is soft and sweet in nature and taste, can be served cold or hot. Panna cotta is a dessert originating from Piedmont, which is part of the northern Italian region bordering Switzerland and France. An 1879 dictionary mentions a dish called latte inglese or English milk, made of cream cooked with gelatine and molded, other sources say that latte inglese is made with egg yolks known to people as thick custard. Another alternative as a substitute for milk fat is green bean milk. Mungbean milk or mungbean milk is one of the processed products which is extracted from peeled green beans. Mung bean has a fairly high protein content of 22% and is a source of important minerals, including calcium and phosphorus. The low fat content in green beans causes food or drinks made from green beans not to smell easily. It can be concluded that panna cotta has good nutritional content with high fat content. So the author is interested in using mung bean milk as a substitute for full cream milk and fibere crÃ¨me as a substitute for fresh cream.